MODEL SERVQUAL DALAM LAYANAN KEAGAMAAN: ANALISIS KEPUASAN JAMAAH HAJI DAN UMROH DI KANTOR KEMENTERIAN AGAMA KABUPATEN OGAN KOMERING ULU - Eka Mustika Riantina; Yurike Natasya (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2024)
This study examines pilgrim satisfaction through the Servqual model (reliability, responsiveness, assurance, empathy, and tangibles) at the Ministry of Religious Affairs Office in Ogan Komering Ulu Regency. A quantitative survey method was applied to 74 randomly selected respondents from a population of 294 prospective pilgrims. Data were collected using a five-point Likert scale questionnaire, validated by Aiken’s V (> 0.70) and reliability tested by Cronbach’s α (> 0.80). Multiple linear regression analysis revealed that all five Servqual dimensions significantly affect pilgrim satisfaction (F-stat = 12.345; p < 0.05), with a determination coefficient (R²) of 0.65. Partially, reliability (β = 0.38; p < 0.01) and assurance (β = 0.29; p < 0.05) emerged as dominant predictors. These findings reinforce Parasuraman et al.’s (1988) propositions in religious services and highlight the need to enhance staff competencies and supporting facilities to optimize empathy and tangible dimensions. This study provides empirical contributions to the development of Servqual models in public sectors with religious values.